Sociocultural Values and Pragmatics of Caste Address Form in Multilingual Pakistani Student and Teacher Discourse - Muhammad Arif Soomro (National Research Mordova State University, 2023)
Introduction. Pakistani universities' multilingual and multicultural classrooms can create communication difficulties when trying to understand the attitude and meanings conveyed by caste address forms in student and teacher discourse. Address forms are influenced by sociocultural values, they reflect speakers' linguistic reality and convey the social structure of the society. Among the variety of address forms in Pakistani English speakers' caste as a category of address form represents their cultural identity and norms. This article aims to present the findings of the study regarding the use of caste as a category of forms of address among multilingual Pakistani English speakers in a university setting. Materials and Methods. The author shares the results based on data collected from a vast range of tools such as discourse completion task questionnaires, open-ended interviews, official letters issued by the universities, and validated by ethnographic observation. A total number of n = 447 responses were received from public sector universities of Pakistan. The analysis of data was based on a mixed method of both quantitative and qualitative approaches and draws on an interdisciplinary theoretical framework based on cultural linguistics, cross- and intercultural pragmatics, cultural studies, theory of address forms, World Englishes, and sociolinguistics. Results. The results reveal that caste address form usage in Pakistani English has socio-pragmatic dynamics. The students and teachers used caste as an address form in a variety of ways that adhere to sociocultural values to achieve their communicative needs. The caste usage showed closeness/intimacy, respect, and informality among both students and teachers. These results suggest that caste as the category of address forms is interpreted as an instrument that interlocutors use to discursively construct appropriate, situation-based aspects of their lingua-cultural identities. The results have implications for language learning and teaching, sociolinguistics, and academic discourse. Discussion and Conclusion. In the multilingual academic setting, this study's results suggest the influence of social and cultural values on the communication etiquettes of interlocutors. Pakistani English speakers adhere to their communication norms acknowledging varieties of sociopragmatic knowledge to achieve communicative needs. To sum up, results reveal variance in the use of caste as a category of address form showing multilingual Pakistani English speakers' cultural and bi-multilingual identity. Their use and choice of address form express respect, intimacy/closeness, and informality at the same time, however, European addressing styles indicate either respect or intimacy.